دور تطبيق TikTok في مهارة الكلام لطلاب شعبة تعليم اللغة العربية بجامعة سومطرة الشمالية الإسلامية الحكومية - Hafifah Umairah Siregar; Darwin Zainuddin (EduInovasi: Journal of Basic Educational Studies, 2024)
Learning Arabic is a complex challenge for students majoring in Arabic Language Education. In the current digital era, information and communication technology has become an integral part of everyday life, and the TikTok application has become a very popular platform among students. This research aims to investigate the role of the TikTok application in learning Arabic. The research method used is a qualitative approach and case study. Data was collected through participant observation, interviews, and analysis of TikTok video content. By using the TikTok application, Arabic language students understand more about learning Arabic and are motivated to speak Arabic and increase their desire to continue learning Arabic through short and interesting videos. The results of the research show that the TikTok application has a significant role in learning Arabic, especially for Maharah Kalam Students of the 2021 Stambuk Arabic Language Education Department at the North Sumatra State Islamic University, Medan.